2011
DOI: 10.1080/15402002.2011.557991
|View full text |Cite
|
Sign up to set email alerts
|

Six-Month Sleep–Wake Organization and Stability in Preschool-Age Children With Autism, Developmental Delay, and Typical Development

Abstract: This study examined sleep–wake patterns in 3 matched comparison groups of preschool-aged children: children with autism (AUT), children with developmental delay (DD) without AUT, and children who are developing typically (TYP). Sleep was assessed via actigraphy and parent-report diaries for 7 consecutive 24-hr periods across 3 time points: at enrollment (n = 194), 3 months later (n = 179), and 6 months after enrollment (n = 173). At each recording period, children in the AUT group slept less per 24-hr period, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…The three studies examining sleep IIV in children with autism and other developmental disabilities were drawn from the same sample of children [7375]. An initial cross-sectional study did not find differences in sleep IIV (i.e., onset IIV, duration IIV, waking IIV, quality IIV) between children with autism, children with a developmental delay (but not autism), or typically developing children [74].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The three studies examining sleep IIV in children with autism and other developmental disabilities were drawn from the same sample of children [7375]. An initial cross-sectional study did not find differences in sleep IIV (i.e., onset IIV, duration IIV, waking IIV, quality IIV) between children with autism, children with a developmental delay (but not autism), or typically developing children [74].…”
Section: Resultsmentioning
confidence: 99%
“…Further analyses found no differences in sleep IIV when children in these three groups were subdivided into those with and without elevated ADHD symptoms [75]. A follow-up study examined sleep IIV over a six-month period and found that children in either of the neurodevelopmental disorder groups had greater duration IIV and quality IIV than their typically developing peers, though within-child variability was greater than between-child variability for all three groups [73]. Less mature developmental age was also associated with greater waking IIV, duration IIV, and quality IIV [74].…”
Section: Resultsmentioning
confidence: 99%
“…28 Accelerometry recordings from 7:00 am to 8:59 pm were used to capture the typical daily wake time cycle for young children. 29,30 …”
Section: Methodsmentioning
confidence: 99%
“…Sleep problems are not a constant in the development of individuals with ASD, but are fairly stable with sleep problems noted across the life course (Cohen, Conduit, Lockley, Rajaratnam, & Cornish, 2014; Croen et al, 2015). Only a few studies directly assess the stability of sleep problems/behaviors in ASD noting short-term stability for 3–6 months without intervention (Anders, Iosif, Schwichtenberg, Tang, & Goodlin-Jones, 2011; Goodlin-Jones et al, 2009) but numerous studies document elevated rates of sleep problems in children, adolescents, and adults using cross-sectional designs (Croen et al, 2015). Sleep problems are more common in individuals with ASD who also have comorbid ADHD, anxiety, depression, or gastrointestinal problems (Klukowski, Wasilewska, & Lebensztejn, 2015).…”
Section: Syndrome/condition Specific Sleep Problemsmentioning
confidence: 99%